2016
DOI: 10.3324/haematol.2016.145136
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibody deficiency and autoinflammatory disease extend the clinical and immunological spectrum of heterozygous NFKB1 loss-of-function mutations in humans

Abstract: The nuclear factor of kappa light polypeptide gene enhancer in B-cells 1 (NF-κB1) is a master regulator of immune and inflammatory responses.1,2 NF-κB1 belongs to the NF-κB/Rel family of transcription factors that consists of five members in humans: NF-κB1 (p105/p50), NF-κB2 (p100/p52), RelA, c-Rel, and RelB. The p105 and p100 precursors are proteolytically processed by the proteasome to generate the shorter p50 and p52 isoforms. Homo-and heterodimers are formed by p50, p52 and the Rel proteins. Unstimulated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 16 publications
1
51
0
Order By: Relevance
“…P9.1 and P9.2 ( NFKB1 p.S302Ffs∗7) both suffered autoimmunehaemolytic anaemia, which is reported in NFKB1 haploinsufficient patients 24 , 25 . Differing AI/I is observed in patients with NKFB1 mutations, ranging from antibody deficiency, Behcet‐like disease, to an autoinflammatory phenotype 26 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…P9.1 and P9.2 ( NFKB1 p.S302Ffs∗7) both suffered autoimmunehaemolytic anaemia, which is reported in NFKB1 haploinsufficient patients 24 , 25 . Differing AI/I is observed in patients with NKFB1 mutations, ranging from antibody deficiency, Behcet‐like disease, to an autoinflammatory phenotype 26 …”
Section: Discussionmentioning
confidence: 94%
“…23 NFKB1 haploinsufficiency (OMIM 616576) P9.1 and P9.2 (NFKB1 p.S302Ffs*7) both suffered autoimmune haemolytic anaemia, which is reported in NFKB1 haploinsufficient patients. 24,25 Differing AI/I is observed in patients with NKFB1 mutations, ranging from antibody deficiency, Behcet-like disease, to an autoinflammatory phenotype. 26 Autoimmunity in a PID cohort W Rae et al NFKB2 dominant negative immunodeficiency (OMIM 615577) P10 (NFKB2 p.R853*) suffered autoimmune alopecia, which is widely reported in patients with dominant negative NFKB2 variants but the renal disease that was present in P10 has not been reported in NKFB2 variants to date.…”
Section: Stat1 Gain Of Function (Omim 614162)mentioning
confidence: 99%
“…We report a novel mutation of NFKB1 in a pediatric patient with cytopenias, lymphadenopathy, and splenomegaly. To the best of our knowledge, this variant has not been reported in previously described NFKB1 cases (Boztug et al 2016;Maffucci et al 2016;Schipp et al 2016;Kaustio et al 2017;Lougaris et al 2017;Dieli-Crimi et al 2018;Fliegauf and Grimbacher 2018;Tuijnenburg et al 2018).…”
Section: Introductionmentioning
confidence: 73%
“…Multiple recent studies have identified variants in NFKB1 as a monogenic cause of immunodeficiency/ immune dysregulation (Table 2) (Maffucci et al 2016;Schipp et al 2016;Kaustio et al 2017;Lougaris et al 2017;Dieli-Crimi et al 2018;Fliegauf and Grimbacher 2018;Tuijnenburg et al 2018). Patients display a wide range of phenotypic heterogeneity including recurrent sinopulmonary infections, viral and fungal infections, autoimmunity, lymphoproliferation, and malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation